Helix 1 tryptophan variants in Galleria mellonella apolipophorin III. (December 2015) - Thistle, Jake; Martinon, Daisy; Weers, Paul M.M.
Graphical abstract: Highlights: Three single tryptophan residues were engineered in helix 1 of apolipophorin III. All three variants are suitable for use as a reporter for local changes in the protein environment upon lipid binding interaction. Introduction of tryptophan 20 and 24 increased the protein stability, resulting in an increased resistance to solubilize phospholipid vesicles. Binding of the most stable W20-apoLp-III apoLp-III variant to modified LDL was compromised. Abstract: Apolipophorin III (apoLp-III) from Galleria mellonella is a critical apolipoprotein aiding in lipid transport and has gained considerable interest for a role in innate immunity. Both functions are likely related and form the rationale to gain a more detailed understanding of the lipid binding properties of this insect apolipoprotein. Tryptophan residues were introduced at positions 16, 20 or 24, all in helix 1 as it may play a critical role in the initial steps of lipid binding. Steady-state fluorescence analysis showed that each tryptophan displayed unique properties, indicating different environments both in lipid-free as in lipid-bound states, and demonstrating potential for use in lipid binding analysis. While α-helical contents of wild-type and the tryptophan variant proteins were similar, W20- and W24-apoLp-III displayed increased protein stability. These variants were significantly slower in their ability to convert phosphatidylcholine vesicles into discoidal lipoproteins, which was employed as a measure for lipid binding. In contrast, W16-apoLp-III displayed decreased protein stability but an order of magnitude higher rate of discoidal lipoprotein formation. This demonstrates an inverse correlation between protein stability and the ability to convert vesicles in discoidal lipoproteins. The most stable W20-apoLp-III variant displayed comprised LDL binding capabilities, indicating a partial loss of function. Thus, there is a delicate balance between helix bundle stability and the ability to bind lipids, and helix 1 may play a critical role in this process.